2019
DOI: 10.3906/vet-1903-27
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of Anaplasma spp. in blood and milk of dairy cattle in the Philippines

Abstract: Anaplasmosis has become a major concern in the cattle industry throughout the world due to its great economic impact. The causative agents, Anaplasma species, are primarily transmitted by ticks, occurring intracellularly within blood cells, with some species being zoonotic. In this study, the presence of Anaplasma spp. was investigated in the blood and milk of dairy cattle in the Philippines. Blood and milk samples were collected from 98 dairy cattle from selected farms in five provinces in the southern part o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
(33 reference statements)
0
3
1
Order By: Relevance
“…A high prevalence of A. marginale was observed in cattle, but it was lower than the prevalence previously reported in a study in Luzon involving two dairy farms (13) and the detection rate in our study in the same region that only included milking dairy cattle (17). The current study included dairy cattle, most of which are Holstein Friesian or Holstein-Sahiwal crosses, as well as the tropical native Philippine cattle commonly raised for beef.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…A high prevalence of A. marginale was observed in cattle, but it was lower than the prevalence previously reported in a study in Luzon involving two dairy farms (13) and the detection rate in our study in the same region that only included milking dairy cattle (17). The current study included dairy cattle, most of which are Holstein Friesian or Holstein-Sahiwal crosses, as well as the tropical native Philippine cattle commonly raised for beef.…”
Section: Discussioncontrasting
confidence: 78%
“…Nevertheless, epidemiological data in the country remains fragmented. Aside from its presence in the blood, we previously reported the detection of A. marginale in the milk of dairy cattle (17). A study previously reported the detection of Ehrlichia in 35 of 246 bovine blood samples through PCR, but the species was not identified (18).…”
Section: Introductionmentioning
confidence: 99%
“…The 16.67% (8/48) bovine A. marginale detection rate in this survey was significantly lower compared to a recent study which reported a 100% Anaplasma spp. detection rate in 21 dairy cattle in the same area [ 8 ]. In the Philippines, hemoplasmas have only been reported in cattle and goats in Cebu [ 13 , 22 ] and dairy cattle and water buffaloes (80%) in Bohol [ 24 ] in the Visayas area.…”
mentioning
confidence: 99%
“…In the current study, the relative abundance of Anaplasma decreased remarkably after a day of refrigeration, indicating that the low temperature at which raw milk was stored was may unsuitable for its growth. Similarly, using nested PCR and sequential analysis, Dela Cruz, Galay, Sandalo, Pilapil‐Amante, and Tanaka (2019) also identified Anaplasma genus in raw milk. Zhang, Chen, et al (2016); Zhang, Lv, et al (2016) annotated Anaplasma phagocytophilum at the species level in fresh healthy goat milk, which was also annotated in this study.…”
Section: Discussionmentioning
confidence: 91%